Remnants of the fall - Rolnick, William B (World Scientific, 2003)
Includes bibliographical references and index; About questions and answers -- The matter we know : properties and principles -- The relativity of space and time -- The quantum properties of nature, part one -- The quantum properties of nature, part two -- Quantum mechanical reality -- The particles of matter -- The basic interactions -- Spacetime symmetries -- "Internal" symmetries : isotopic spin -- Particle flavors -- A larger flavor symmetry : entrance to the land of quarks -- About gauge theories -- The strong interaction : quantum chromodynamics (QCD) -- The weak interaction : the foot-hills -- The electroweak interaction and the standard model -- Above and beyond -- The role of experiments and experimentalists -- The experimental connection -- Particle accelerators and detectors